Managerial Myopia and Firm Green Innovation: Based on Text Analysis and Machine Learning - Liu, Xin (Frontiers in Psychology, 2022)
Green innovation plays an important role in reducing pollution and promoting sustainable development. However, not all managers, as decision-makers of enterprises, have a long-term vision to implement green innovation. The impact of managerial myopia on firm green innovation has not been examined by existing literature. Drawn on time-oriented theory in social psychology and upper echelon theory in management, this paper puts forward the relationship between managerial myopia and firm green innovation, and then constructs a managerial myopia index by text analysis and machine learning. Using a sample of publicly listed Chinese firms from 2009 to 2020, this paper finds that managerial myopia is significantly negatively associated with firms’ green innovation. Every one standard deviation increase in managerial myopia makes enterprise green innovation decrease by about 1.9% standard deviation. Further analysis reveals that equity incentives and institutional investors both weaken the negative effect of managerial myopia on green innovation. This study contributes to the literature on green innovation and upper echelons theory and it also has several implications for firms’ engagement in green innovation.